Rare cases of laboratory tests discrepancies in diagnostics of pediatric Burkitt lymphoma/leukemia - I. A. Demina; O. I. Illarionova1; T. Yu. Verzhbitskaya; G. A. Tsaur; E. B. Rusanova; M. V. Gorchakova; E. E. Zueva; M. B. Belogurova; G. I. Uleiskaya; L. A. Shchekina; A. N. Kazakova; E. A. Zerkalenkova; et al. (Онкогематология, 2018)
Introduction. The main features of bone marrow blasts cells in Burkitt lymphoma/leukemia (BL) are L3 morphology, mature immunophenotype of blasts with surface IgM expression, and presence of typical MYC gene rearrangements.The aim of the study was to show discrepancy examples in laboratory signs of BL.Patients and methods. 10 patients (8 boys and 2 girls) aged 1 to 18 years were included in the present study. The inclusion criterion was the identification of discrepancies between flow cytometric, morphological and cytogenetic data.Results. In 2 cases there were no rearrangements of the MYC gene. In 2 patients, the L2 morphological variant went against the presence of typical MYC gene rearrangements. In one case, undifferentiated blasts cells were described by morphology together with presence of surface IgM, and atypical genetics. In 8 patients, there was no expression of surface IgM. Of these, patients with absence of cytomorphological data cytometric and genetic data were controversial.Сonclusion. The cases presented in this study and the cases described in the literature demonstrate the importance of an attentive and comprehensive approach in evaluating the results of laboratory tests in the diagnosis of BL.